2007
DOI: 10.1111/j.1745-3933.2006.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

First e-VLBI observations of GRS 1915+105

Abstract: We present results from the first successful open call e-VLBI science run, observing the X-ray binary GRS 1915+105. e-VLBI science allows the rapid production of VLBI radio maps, within hours of an observation rather than weeks, facilitating a decision for follow-up observations. A total of 6 telescopes observing at 5 GHz across the European VLBI Network (EVN) were correlated in real time at the Joint Institute for VLBI in Europe (JIVE). Constant data rates of 128 Mbps were transferred from each telescope, giv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Due to selection effects that limit most observations to periods of strong radio emission, only a few high-resolution observations have been taken in this state. e-EVN observations taken in this state during April 2006 (Rushton et al 2007) showed no evidence for any compact jet, unlike the jet observed by Fuchs et al (2003), suggesting no outflow of material. Likewise, MERLIN observations taken in 1999 showed no large scale structure, despite X-rays flares, suggesting a de-coupling of the accretion disk to any radio emission.…”
Section: No Detected Jet -'Radio Quiet State/short Flares'mentioning
confidence: 52%
“…Due to selection effects that limit most observations to periods of strong radio emission, only a few high-resolution observations have been taken in this state. e-EVN observations taken in this state during April 2006 (Rushton et al 2007) showed no evidence for any compact jet, unlike the jet observed by Fuchs et al (2003), suggesting no outflow of material. Likewise, MERLIN observations taken in 1999 showed no large scale structure, despite X-rays flares, suggesting a de-coupling of the accretion disk to any radio emission.…”
Section: No Detected Jet -'Radio Quiet State/short Flares'mentioning
confidence: 52%
“…Due to selection effects that limit most observations to periods of strong radio emission, only a few high‐resolution observations have been taken in this state. European VLBI Network (e‐EVN) observations taken in this state during 2006 April (Rushton et al 2007) showed no evidence for any compact jet, unlike the jet observed by Fuchs et al (2003), suggesting no outflow of material. Likewise, MERLIN observations taken in 1999 showed no large‐scale structure, despite X‐rays flares, suggesting a de‐coupling of the accretion disc to any radio emission.…”
Section: Discussionmentioning
confidence: 82%
“…X-ray observations with the ASM instrument onboard the RXTE satellite and 15-GHz radio monitoring with the Ryle Telescope in1999, 2003-2007 (no RT data were available in 2006-2007. The dotted lines denote the MERLIN 18-cm epochs, showing that the source was in different X-ray 'states' during the observations.…”
mentioning
confidence: 99%
“…the correlator). This technique is under continuous development and has been successfully used for the study of transient phenomena (Rushton et al 2007; Tudose et al 2007).…”
Section: Observations and Analysismentioning
confidence: 99%